Clustering of genomic breakpoints at the MLL locus in therapy-related acute leukemia with t(4;11)(q21;q23) - Hasan, Syed Khizer; Barba, Gianluca; Metzler, Markus; Divona, Mariadomenica; Ottone, Tiziana; Cicconi, Laura; Falini, Brunangelo; Mecucci, Cristina; Lo-Coco, Francesco (Genes Chromosomes & Cancer, 2014)
Genomic characterization of translocation breakpoints is relevant to identify possible mechanisms underlying their origin. The consistent association of anthracylines (e.g., epirubicin and idarubicin) in inducing therapy-related acute leukemias (t-AL) with mixed lineage leukemia (MLL) gene rearrangement suggests that MLL translocations are causative events for t-AL. Using asymmetric multiplex PCR strategy followed by direct DNA sequencing, we characterized the genomic breakpoints of the MLL and AFF1 genes in two patients who developed t-AL with t(4;11)(q21;q23). Chemotherapeutic treatment of the primary disease in both patients included topoisomerase II (topo II) targeting agents. In one case, the MLL breakpoint was located in intron 9 at nucleotide position chr11:118354284 while the AFF1 breakpoint was in intron 3 at nucleotide position chr4:87992070. The breakpoint junction sequences revealed an insertion of two nucleotides at the MLL-AFF1 junction. In the other patient, the MLL breakpoint was located in intron 11 at nucleotide position chr11:118359130-32 and the AFF1 break was in intron 3 at nucleotide position chr4:87996215-17. The MLL breakpoint found in the latter patient was identical to that of two previously reported cases, strongly suggesting the presence of a preferential site of DNA cleavage in the presence of topo II inhibitor. In addition, microhomologies at the breakpoint junctions were indicative of DNA repair by the non-homologous end joining (NHEJ) pathway. This study further supports the evidence that MLL breakpoints in therapy-related acute leukemia with MLL-AFF1 are clustered in the telomeric half of the breakpoint cluster region that contains topo II recognition sites.
EVALuna2:18880